Physiological, anthropometric, and performance characteristics of rugby sevens players - Higham, D. G.; Pyne, D. B.; Anson, J. M.; Eddy, A. (International Journal of Sports Physiology and Performance, 2013)
Although the characteristics of 15-a-side rugby union players have been well defined, there is little information on rugby sevens players. Purpose: The authors profiled the anthropometric, physiological, and performance qualities of elite-level rugby sevens players and quantified relationships between these characteristics. Methods: Eighteen male international rugby sevens players undertook anthropometric (body mass, height, sum of skinfolds, lean-mass index), acceleration and speed (40-m sprint), muscle-power (vertical jump), repeated- sprint-ability (6 × 30-m sprint), and endurance (Yo-Yo Intermittent Recovery test and treadmill VO2max) testing. Associations between measurements were assessed by correlation analysis. Results: Rugby sevens players had anthropometric characteristics (body mass 89.7 ± 7.6 kg, height 1.83 ± 0.06 m, sum of 7 skinfolds 52.2 11.5 mm; mean ± SD) similar to those of backs in international 15-player rugby union. Acceleration and speed (40-m sprint 5.11 ± 0.15 s), muscle-power (vertical jump 66 ± 7 cm), and endurance (VO2max 53.8 ± 3.4 mL/kg·min) qualities were similar to, or better than, those of professional 15-a-side players. Coefficients of variation ranged from 2.5% to 22%. Relative VO2max was largely correlated with Yo-Yo distance (r = .60, .21-.82; 90% confidence interval) and moderately correlated with 40-m sprint time (r = -.46, -.75 to -.02) and repeated-sprint ability (r = -.38, -.72 to .09). Conclusions: International rugby sevens players require highly developed speed, power, and endurance to tolerate the demands of competition. The small between-athletes variability of characteristics in rugby sevens players highlights the need for relatively uniform physical and performance standards in contrast with 15-a-side players.